Multitasking SecB chaperones in bacteria - Sala, Ambre; Bordes, Patricia; Genevaux, Pierre (Frontiers in Microbiology, 2014)
Protein export in bacteria is facilitated by the canonical SecB chaperone, which binds to unfolded precursor proteins, maintains them in a translocation competent state and specifically cooperates with the translocase motor SecA to ensure their proper targeting to the Sec translocon at the cytoplasmic membrane. Besides its key contribution to the Sec pathway, SecB chaperone tasking is critical for the secretion of the Sec-independent heme-binding protein HasA and actively contributes to the cellular network of chaperones that control general proteostasis in Escherichia coli, as judged by the significant interplay found between SecB and the Trigger Factor, DnaK and GroEL chaperones. Although SecB is mainly a proteobacterial chaperone associated with the presence of an outer membrane and outer membrane proteins, secB-like genes are also found in Gram-positive bacteria as well as in certain phages and plasmids, thus suggesting alternative functions. In addition, a SecB-like protein is also present in the major human pathogen M. tuberculosis where it specifically controls a stress-responsive toxin-antitoxin (TA) system. This review focuses on such very diverse chaperone functions of SecB, both in E. coli and in other unrelated bacteria.